Study the Effect of Annealing Temperature on the Structural, Optical and Electrical Properties of ZnS Thin Films - Al-Fawade, E. M. N.; Naji, I. S.; Mohammed, H. I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The structural, optical and electrical properties of ZnS films prepared by vacuum evaporation technique on glass substrate at room temperature and treated at different annealing temperatures (323, 373, 423)K of thickness (0.5)Âµm have been studied. The structure of these films is determined by X-ray diffraction (XRD). The X-ray diffraction studies show that the structure is polycrystalline with cubic structure, and there are strong peaks at the direction (111).The optical properties investigated which include the absorbance and transmittance spectra, energy band gab, absorption coefficient, and other optical constants. The results showed that films have direct optical transition. The optical band gab was found to be in the range to (2.96-3.06)eV with increasing annealing temperatures. The electrical properties of these films have been studied, it was observed that D.C conductivity at room temperature decreases with the increase of annealing temperatures, and the mechanism of conductivity occurs in two ranges of temperature, from Hall measurements the conductivity for all samples of ZnS films is n-type.